x2 - 12x + 36 = (x - 6)2
x2 + 12x - 5 = 0x2 + 12x - 5 + 5 = 0 + 5x2 + 12x = 5x2 + 12x + (12/2)2 = 5 + (12/2)2x2 + 12x + (6)2 = 5 + 36(x + 6)2 = 41 (square root of both sides)x + 6 = ± √41x + 6 - 6 = -6 ± √41x = -6 ± √41x ≈ -6 + 6.4 = -0.4x ≈ -6 - 6.4 = -12.4
If the equasion is 12x+6-8x-4x-3+12 then the answer is 15.
42
6x2 + 7x = 56x2 + 7x - 5 = 0x =[ -7 ± √[72 - 4(6)(-5)] ]/2(6)x = [-7 ± √(49 + 120)]/12x = (-7 ± √ 169)/12x = (-7 ± 13)/12x = (-7 + 13)/12 or x = (-7 - 13)/12x = 6/12 = 1/2 orx = -20/12 = - 5/3
(12x - 6)(12x + 6)
6*3-6*2-12x v v 18 - 12-12x v v 6-24x -6 -6 something like that..
12x - 2x = 10
12x - 6 = 10x +2 12x - 10x = 2 + 6 2x = 8 x = 4
8x-3+6x-1 = 12x+614x-4 = 12x+614x-12x = 6+42x = 10x = 5
x2 - 12x + 36 = (x - 6)2
-6
12x - 8 = 10x + 42x = 12x = 6
If that's 12x + 18, that can be factored to 6(2x + 3)
x2-12x+36 = (x-6)2
x2 + 12x - 5 = 0x2 + 12x - 5 + 5 = 0 + 5x2 + 12x = 5x2 + 12x + (12/2)2 = 5 + (12/2)2x2 + 12x + (6)2 = 5 + 36(x + 6)2 = 41 (square root of both sides)x + 6 = ± √41x + 6 - 6 = -6 ± √41x = -6 ± √41x ≈ -6 + 6.4 = -0.4x ≈ -6 - 6.4 = -12.4
If you're looking to solve for x, you can do so as follows: x2 + 12x - 6 = 0 x2 + 12x + 36 = 42 (x + 6)2 = 42 x + 6 = ± √42 x = -6 ± √42